2019
DOI: 10.3390/min9100629
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Charge on the Separation of Pyrite from Serpentine by Flotation

Abstract: Serpentine, a magnesium silicate mineral with positive surface charge in many sulfide ores around the world, usually deteriorates the flotation behavior by covering the target mineral surface. In this paper, the effect of surface potential regulation on serpentine flotation was revealed by flocculation experiments, zeta potential measurements, infrared spectrum analysis, and DLVO theoretical calculations. The experimental results of flocculation and sedimentation show that heterogeneous coagulation easily occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This is due to its precipitation and surface charge which may contribute to the adsorption of polar crude components (asphaltene) onto the rock surface, thus resulting in wettability alteration. Pyrite surface charge has a significant effect from a solid–fluid interaction point of view and is highly dependent on the medium pH, which also is controlled by the amount and type of salts present as well as the environmental (anoxic or oxygen-rich) conditions. Weerasooriya and Tobschall report the effect of pH on the surface charge of pyrite in pyrite–water interactions and concluded that the surface charge is controlled by the presence of H + , OH – , and Fe 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to its precipitation and surface charge which may contribute to the adsorption of polar crude components (asphaltene) onto the rock surface, thus resulting in wettability alteration. Pyrite surface charge has a significant effect from a solid–fluid interaction point of view and is highly dependent on the medium pH, which also is controlled by the amount and type of salts present as well as the environmental (anoxic or oxygen-rich) conditions. Weerasooriya and Tobschall report the effect of pH on the surface charge of pyrite in pyrite–water interactions and concluded that the surface charge is controlled by the presence of H + , OH – , and Fe 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Coal slurry is a complex mixture with multiple components and phases, in which the colloidal particles are coagulated and aggregated through the action of charge neutralization, patch aggregation, bridge connection, and sweep flocculation in series or synchronously for negatively charged particles resulting from the existence of preferential dissociation (or dissolution), adsorption and ionization, lattice substitution, and other phenomena [39,40]. Although it is difficult to separate these mechanisms throughout the aggregation process, analyzing zeta potential variation and particle removal as a function of coagulant dosage might provide some insight [41]. As shown in Figure 3, similar charge properties were observed upon injection of Mg 2+ , Ca 2+ , Al 3+ , and Fe 3+ .…”
Section: Zeta Potentialmentioning
confidence: 99%
“…Due to the unreasonable payoff distribution system [36,44,72] of mineral resources and the inadequate supervision of local government, mining enterprises fail to fulfill their social responsibilities, which will bring local community some bad effects, such as environmental pollution, ecological damage [19,35,58], low level of resource utilization and losses of social welfare. Therefore, local government should improve the distribution system of mineral resources development payoff and strengthen the supervision and punishment.…”
Section: Game Between Local Government and Local Communitymentioning
confidence: 99%